2008
DOI: 10.1161/circresaha.107.170662
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin Domain Receptor 1 ( Ddr1 ) Deletion Decreases Atherosclerosis by Accelerating Matrix Accumulation and Reducing Inflammation in Low-Density Lipoprotein Receptor–Deficient Mice

Abstract: Abstract-Collagens are abundant within the atherosclerotic plaque, where they contribute to lesion volume and mechanical stability and influence cell signaling. The discoidin domain receptor 1 (DDR1), a receptor tyrosine kinase that binds to collagen, is expressed in blood vessels, but evidence for a functional role during atherogenesis is incomplete. In the present study, we generated Ddr1 ϩ/ϩ ;Ldlr Ϫ/Ϫ and Ddr1 Ϫ/Ϫ ;Ldlr Ϫ/Ϫ mice and fed them an atherogenic diet for 12 or 24 weeks. Targeted deletion of Ddr1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 46 publications
6
76
0
1
Order By: Relevance
“…4 -6 A number of studies have shown that DDR1 is implicated in carcinogenesis, inflammation, atherosclerosis, and fibrogenesis. [7][8][9][10][11][12] Consistent with an important pathogenetic role in vascular diseases, 8,[13][14][15] we have demonstrated that DDR1-deficient mice were protected against renal vascular lesions induced by a long-term infusion of angiotensin II, a model in which hemodynamic alterations and vascular remodeling play a major role. 11 Whether DDR1 may contribute to the initiating mechanisms and the progression of renal fibrosis irrespective of the initial cause remains unclear.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…4 -6 A number of studies have shown that DDR1 is implicated in carcinogenesis, inflammation, atherosclerosis, and fibrogenesis. [7][8][9][10][11][12] Consistent with an important pathogenetic role in vascular diseases, 8,[13][14][15] we have demonstrated that DDR1-deficient mice were protected against renal vascular lesions induced by a long-term infusion of angiotensin II, a model in which hemodynamic alterations and vascular remodeling play a major role. 11 Whether DDR1 may contribute to the initiating mechanisms and the progression of renal fibrosis irrespective of the initial cause remains unclear.…”
mentioning
confidence: 65%
“…Such a protective effect of DDR1 deletion secondary to its antiinflammatory effect has been also demonstrated in a model of atherosclerosis in mice. 8 Moreover, Gross et al 25 recently studied the role of DDR1 in the kidney of Col4A3-deficient mice and suggested that podocyte-matrix interactions via DDR1 may play a role in glomerular injury in Alport syndrome. DDR1 deficiency was also associated with reduced inflammation in the latter study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a DDR1 knock-out is associated with increased plaque formation in murine arteriosclerosis models [30][31][32]. On the other hand, as mentioned above, DDR1 is also a target of imatinib and depending on the model analyzed, DDR1-inhibition has even been reported to protect from arterioslerosis [33].…”
Section: Other Severe Non-hematologic Events Observed During Nilotinibmentioning
confidence: 99%
“…That such an approach is feasible has been borne out in studies in which blockage of T cells reactive to native lipoprotein ApoB100 (4) or mucosal or subcutaneous immunization with HSP65 (9, 10), oxidized LDL (11), native ␤2-glycoprotein I (12), or apolipoprotein B-100 peptide (13,14) have been shown to be atheroprotective. Collagens can compose up to 60% of the total protein content in atherosclerotic plaques (15) and stimulate the growth and inflammation of atheromas (16). We have shown previously that interleukin 17-dependent autoimmunity to type V collagen col(V)) is a consistent feature of atherosclerosis in advanced CAD in humans and in Apoe Ϫ/Ϫ mice on a high-fat diet (17).…”
mentioning
confidence: 99%